2020
DOI: 10.2478/sues-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Poverty in Nigeria: Keynesian Vs Monetary Theory of Poverty

Abstract: This study comparatively investigates the impacts of fiscal and monetary policies on poverty in Nigeria from 1986 to 2018. Using the Ordinary Least Square and Standardized or Beta Coefficient approach, we found that the Nigerian political system plays a vital role on a large number of its citizens living in extreme poverty. Other factors identified as the likely causes of poverty are insurgencies, terrorism, and low productivity among others. Also, monetary policy is more important in alleviating poverty than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Keynesian economic theory, developed by Lord John Maynard Keynes, emphasises the importance of government intervention through fiscal policy to stimulate aggregate demand and promote economic growth (Elliott, 1998). According to Keynesian theory, government spending can directly reduce poverty by stimulating economic activity and creating employment opportunities (Maku et al, 2020). By injecting money into the economy, government spending increases demand, production levels, and incomes, reducing poverty and improving living standards.…”
Section: Theoretical Argumentsmentioning
confidence: 99%
“…Keynesian economic theory, developed by Lord John Maynard Keynes, emphasises the importance of government intervention through fiscal policy to stimulate aggregate demand and promote economic growth (Elliott, 1998). According to Keynesian theory, government spending can directly reduce poverty by stimulating economic activity and creating employment opportunities (Maku et al, 2020). By injecting money into the economy, government spending increases demand, production levels, and incomes, reducing poverty and improving living standards.…”
Section: Theoretical Argumentsmentioning
confidence: 99%
“…Since the inception of the present democratic dispensation in 1999, it was assumed democracy will usher in a participatory governance system that will translate to reduced poverty and improved living standards as a dividend of democracy, it has been observed and documented that Nigeria's poverty situation has gone from bad to worse (Maku, Tella, & Fagbohun, 2020). Omoyibo (2013) inferred that the marginalization by government has made rural dwellers more vulnerable to poverty than their urban counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria's government is unable to meet the needs of the public, and is not even accountable and transparent to its citizens (Adeleke & Charles, 2016). Maku et al (2020) observed that Nigeria's political system plays a significant negative role on a large number of its citizen living in extreme poverty. Farinde (2014) found that lack of access to loans, poor transport system to the market, and ineffective storage facilities were problems facing rural farmers in Egbedore, Irepodun and Orolu Local Government Areas of Osun State.…”
Section: Introductionmentioning
confidence: 99%